1993
DOI: 10.1038/bjc.1993.386
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of prolonged continuous infusion of low dose recombinant interleukin-2 in melanoma and renal cell cancer. Part II: Immunological aspects

Abstract: Previously we described the clinical aspects of a phase I study of prolonged continuous infusion of low-dose recombinant interleukin-2 (rIL-2). In the present paper we report several immunological effects in 13 patients with melanoma and renal cell cancer treated on an out-patient basis with rIL-2 for uninterrupted periods ranging from 5 to 18 weeks. Groups of three patients were treated at following dose levels 0.18, 0.6, 1.8 or 6 x 10(6) IU m-2 24 h-1 and one patient was treated with 3 x 10(6) IU m-2 24 h-1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
2

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
1
12
2
Order By: Relevance
“…Janssen et al and others have shown that T-cell activation and expansion also occur within the first weeks of treatment and appear to be transient (Thompson et al, 1989;Yoshino et al, 1991;Janssen et al, 1993). It is likely that we missed the signs of T-cell activation because of the timing of the immunological analysis in our study (Vlasveld et al, 1993).…”
contrasting
confidence: 39%
See 1 more Smart Citation
“…Janssen et al and others have shown that T-cell activation and expansion also occur within the first weeks of treatment and appear to be transient (Thompson et al, 1989;Yoshino et al, 1991;Janssen et al, 1993). It is likely that we missed the signs of T-cell activation because of the timing of the immunological analysis in our study (Vlasveld et al, 1993).…”
contrasting
confidence: 39%
“…Continuous and prolonged treatment with rIL-2 leads to a sustained increase in the number of natural killer (NK) cells and enhanced NK activity (Caligiuri et al, 1993;Vlasveld et al, 1993). Janssen et al and others have shown that T-cell activation and expansion also occur within the first weeks of treatment and appear to be transient (Thompson et al, 1989;Yoshino et al, 1991;Janssen et al, 1993).…”
mentioning
confidence: 99%
“…Despite encouraging results (response rates of 14-30%, with complete and lasting remissions in approximately 3-5% of patients), the use of highdose rIL-2 results in severe toxicity and some drug-related fatalities (Rosenberg et al, 1987;West et al, 1987). Lower doses of rIL-2 given both alone and in combination with rIFNa were associated with less acute toxicity, although with similar response rate and immunological activity as high-dose schedules (Caligiuri et al, 1990;Schneekloth et al, 1993;Vlasveld et al, 1993). Again, only these patients stable or responding after one or two cycles continued to be treated.…”
mentioning
confidence: 99%
“…The rationale for this approach was based on the following assumptions: (1) low-dose rIL-2 displays anti-tumour effects and immunomodulant activity selectively addressed to the expansion of natural killer cells and of antigen-stimulated T lymhocytes (Caligiuri, 1993;Vlasveld et al, 1993), whereas high-dose rIL-2 can reduce immune responsiveness both depressing delayed-type hypersensitivity and inducing programmed T-cell death (Wiebke et al, 1988;Lenardo, 1991); (2) the expansion of lymphocyte subsets induced by rIL-2 lasts for 1 or 2 months from the end of the treatment (Sondel et al, 1988;Schneekloth et al, 1993); (3) reiterated low-dose immunotherapy given on a regular basis could boost immune responsiveness, eventually overcoming tumour-induced anergy (Caligiuri, 1993).…”
mentioning
confidence: 99%
“…Sir -We read with interest the paper of Vlasveld et al (1993), in which they report on the immunological aspects of constant infusion of low-dose recombinant interleukin 2 (IL-2) in melanoma and renal cell carcinoma patients, including the possible activation of T cells. When measured at weeks 0, 3 and later, they found that the number of T cells decreased, the CD4/CD8 ratios did not change, and there was no increased expression of CD25 and CD27, and no increased proliferation upon stimulation of peripheral blood lymphocytes with CD3 monoclonal antibody (MAb) with or without CD28 MAb.…”
mentioning
confidence: 99%